An investigation on PMS attributes in service organisations in Malaysia - Mohd Amir, Amizawati; Nik Ahmad, Nik Nazli; Mohamad, Muslim Har Sani (Emerald Group Publishing Limited, 2010)

(untitled)
The purpose of this paper is to make a contribution to the performance measurement system (PMS) literature by concentrating on the service context. Providing a Malaysian perspective on PMS design, the study aims to identify the desirable PMS attributes that are perceived to be important for the service sector. Data were collected by administering a mail questionnaire survey to top-level management of private service firms operating in Malaysia. The sampling frame was based on information provided by the Department of Statistics, Malaysia, and the Central Bank of Malaysia. An extensive search of directories/portals was undertaken to compile the mailing list of each service sector. Samples were randomly selected from the list using proportionate stratified sampling. The findings suggest that service firms placed greater emphasis on elements of performance evaluation, benchmarking, timeliness and precise PMS information. Differentiation strategy and intensity of competition are the most prominent factors that influence the choice of PMS attributes. The limitation of the study pertains to the low response from the foreign-owned service firms operating in Malaysia, thus limiting the generalisability of the findings to local-owned firms. To service managers, the evidence demonstrates the relevance of PMS in service firms, where the greater strategic uncertainty and intensity of market competition requires greater reliance on contemporary PMS attributes. The evidence indicates the applicability of PMS in managing both professional service and mass service firms that removed the traditional view that all service activities are unique.